Senyawa Sitotoksik dari Fraksi Diklorometana Kulit Terong Ungu (Solanum melongena L.) Terhadap Sel Kanker Payudara T47D - Ari Widiyantoro; Harlia Harlia; Banu Prasetya (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2021)
Eggplant (Solanum melongena L.) is a plant that contains antioxidants and potentially as a cancer drug. This study was conducted to identify the cytotoxic activity of secondary metabolite compound against T47D breast cancer cells based on the IC50 value. Isolation Eggplant peel was carried out in several steps, such as maceration, partition, and chromatography.The result 1H-NMR (DMSO, 500 MHz) analysis optained a chemical shift of δ 0.86 ppm (1H,m), δ 1.44 ppm (1H,s), δ 1.34 ppm (2H, brs), δ 1.62 ppm (1H, m), δ 3.31 ppm (4H, brs), δ 3.73 ppm (1H, t), dan δ 7.69 ppm (1H,m). Based on the chemical shift 3 ' isolate tends to have similarities to the aglycon pregnan compound steroids. The results showed that the dichloromethane fraction obtained IC50 values of 160.79 µg / mL and the isolate obtained IC50 values of 124.44 µg / mL. The IC50 value obtained by the dichloromethane fraction and isolate was classified as moderate cytotoxic so that it could be used to prevent and inhibit the growth of cancer cells.